Fuzzy AHP Based New Questionnaire Process for Improving Judgments Under Agile Software Development Framework - Mohd. Haroon, Sangeeta Mishra (International Journal of Intelligent Systems and Applications in Engineering, 2024)
An efficient approach of risk assessment that uses a questionnaire to get expert replies is the fuzzy analytical hierarchy process (FAHP). However, the FAHP has significant challenges to establish a consistent judgment matrix & determination of the fuzzy membership function (MF). This study suggests a brand-new consultation procedure to address the triangular MF FAHP’s prior issues. The suggested procedure includes a newly constructed questionnaire and a novel scheme to figure out the fuzzy MF. Responses of experts to the questionnaire were used to build a consistent judgment matrix and determine the membership function. For the intent of proving the proposed scheme’s viability, it is used to the security assessment in agile software development. In the case study, the judgment matrix is created using both the classic and new questionnaires. The outcomes demonstrate that judgment matrix established using the proposed approach may produce a consistent judgment matrix and determine triangular fuzzy MF. The proposed questionnaire, as opposed to the standard one, may be helpful for quickly and conveniently gathering expert opinions.